2011
DOI: 10.1007/s00034-011-9319-4
|View full text |Cite
|
Sign up to set email alerts
|

A Convolution and Correlation Theorem for the Linear Canonical Transform and Its Application

Abstract: As a generalization of the fractional Fourier transform (FRFT), the linear canonical transform (LCT) plays an important role in many fields of optics and signal processing. Many properties for this transform are already known, but the correlation theorem, similar to the version of the Fourier transform (FT), is still to be determined. In this paper, firstly, we introduce a new convolution structure for the LCT, which is expressed by a one dimensional integral and easy to implement in filter design. The convolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 29 publications
1
48
0
Order By: Relevance
“…It is seen from the results of Figs. 2 and 3 that the proposed weighted convolution theorem gives better results than the convolution theorem by Deng et al (2006) and Wei et al (2012;2009), as the results given by the proposed theorem resemble maximally the shape of the LCT of the triangular function. Further, an application of filtering was presented with the proposed convolution theorem and it was found that with the help of proposed theorem the signal is recovered with a minimum mean square error.…”
Section: Resultsmentioning
confidence: 83%
See 4 more Smart Citations
“…It is seen from the results of Figs. 2 and 3 that the proposed weighted convolution theorem gives better results than the convolution theorem by Deng et al (2006) and Wei et al (2012;2009), as the results given by the proposed theorem resemble maximally the shape of the LCT of the triangular function. Further, an application of filtering was presented with the proposed convolution theorem and it was found that with the help of proposed theorem the signal is recovered with a minimum mean square error.…”
Section: Resultsmentioning
confidence: 83%
“…The convolution theorem in the LCT domain given by Deng et al (2006) and Wei et al (2012;2009) is compared with the proposed convolution theorem by simulating on system with an Intel core TM i3-330M 2.13 GHz processor with 3 GB RAM. The convolution operation of a rectangular function x(t) of unit amplitude is performed with itself, i.e., (x ⊗ x)(t).…”
Section: Simulation Resultsmentioning
confidence: 99%
See 3 more Smart Citations